Vietnam in the China Plus One Strategy: Geoeconomic Hedging and Middle-Power Agency in Indo-Pacific Supply Chains - Thi Mong Tuyen Tran (Parahyangan Center for International Studies, 2025)
This article analyzes Vietnam’s strategic repositioning in global supply chains in the context of intensifying U.S.–China rivalry. As multinational corporations implement “China Plus One” strategies to mitigate geopolitical risk and supply chain concentration, Vietnam has emerged as a key destination, benefitting from its geographic proximity to China, cost-effective labor, expanding trade architecture, and proactive regulatory reforms. Yet this shift is not solely driven by firm-level dynamics; it is also the result of Vietnam’s deliberate geoeconomic strategy. Drawing on hedging theory, the article contends that Vietnam employs a calibrated mix of economic diversification, institutional flexibility, and strategic ambiguity to maximize autonomy while avoiding overdependence on any major power. Through empirical examination of foreign direct investment trends, trade commitments, technological upgrading, and participation in both U.S.- and China-led regional initiatives, the paper conceptualizes Vietnam’s approach as “geoeconomic hedging.” It introduces the term “Vietnam Plus One” to describe the country’s emerging role not only as a relocation site but also as a catalyst for broader regional diversification. By extending the logic of hedging beyond the security domain into economic statecraft, this study contributes to ongoing debates on middle-power agency, regional order, and the restructuring of global production networks in the Indo-Pacific. Key words: China Plus One strategy, Vietnam Plus One strategy, geoeconomics hedging, global supply chains, middle power diplomacy